2022
DOI: 10.3390/w14182854
|View full text |Cite
|
Sign up to set email alerts
|

Land-Use and Land Cover Is Driving Factor of Runoff Yield: Evidence from A Remote Sensing-Based Runoff Generation Simulation

Abstract: The spatial distribution of water storage capacity has always been the critical content of the study of saturation-excess runoff. Xin′anjiang model uses the water storage capacity curve (WSCC) to characterize the distribution of water storage capacity for runoff yield calculation. However, the mathematical and physical foundations of WSCC are unclear, which is impossible to simulate runoff generation with complex basins accurately. To fill this gap, we considered the dominant role of basin physical characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 93 publications
0
0
0
Order By: Relevance
“…(2) Difference between LU and PREP on AWRs change Most studies have shown that surface vegetation can reduce water resources in basins, but the degree of reduction has not been quantified [54,55]. Through the VAR model constructed in this study, it was found that the contribution rates of AD, WD, GD, CD, and PREP to changes in AWRs were 23.76%, 4.40%, 4.34%, 4.56%, and 6.09%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…(2) Difference between LU and PREP on AWRs change Most studies have shown that surface vegetation can reduce water resources in basins, but the degree of reduction has not been quantified [54,55]. Through the VAR model constructed in this study, it was found that the contribution rates of AD, WD, GD, CD, and PREP to changes in AWRs were 23.76%, 4.40%, 4.34%, 4.56%, and 6.09%, respectively.…”
Section: Discussionmentioning
confidence: 99%